Getting educated at ESNAM: the choice of puppetry in an art school (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
The Ecole Nationale Supérieure des arts de la Marionnette was created in1987 by Margareta Niculescu in Charleville-Mézières, at the heart of the Institut International de la Marionnette. Resourceful educational methods renewed both initial and professional training alike as artists were invited to come and teach and convey their knowledge. A balance between learning fundamentals (construction, dramatic acting, manipulation, body and movement, voice) and artistic workshops directed towards personal and collective projects structures a 3-year curriculum. The School’s move into new premises, thus allowing for an increase in the 3-year cycle rhythm, and the forthcoming creation of a new puppeteer-actor diploma situate this training and this trade in the development and recognition of puppetry arts in France.Keywords: Resourceful educational methods. Learning fundamentals. Initial training. Puppeteer-actor. Trade.